How to Forget the Unforgettable? On Collective Trauma, Cultural Identity, and Mnemotechnologies. Issue 3 (3rd July 2017) - Aydin, Ciano
ABSTRACT: Nietzsche's notion of "active forgetting" is employed to better understand the disruptive and destructive influence of collective trauma on cultural identity. Throughout the article genocide is taken as a cause of extreme trauma and used to illustrate this impact. Active forgetting in this context should not be confused with memories fading away; it is rather a positive and active force, a capacity which an individual, a society, or a culture needs to prosper. This notion provides guidance on how to banish the trauma to the extent that it ceases to paralyze the traumatized group. Technological skills that release negative emotions and ideas generated by the trauma from the collective memory—mnemotechnologies—are required to restore the capacity of forgetting.